2003
DOI: 10.1111/j.0014-3820.2003.tb01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Mechanisms of Selection on a Family-Diagnostic Trait: Evidence From Experimental Manipulation and Lifetime Fitness Selection Gradients

Abstract: Plant traits that show little variation across higher taxa are often used as diagnostic traits, but the reason for the stasis of such traits remains unclear. Wild radish, Raphanus raphanistrum, exhibits tetradynamous stamens (four long and two short, producing a dimorphism in anther height within each flower), as do the vast majority of the more than 3,000 species in the Brassicaceae. Here we examine the hypothesis that selection maintains the stasis of dimorphic anther height by investigating the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Thus, if pollen removal is correlated with seed-siring success, this would mean selection to decrease dimorphism and could explain why honey bees select for decreased dimorphism. However, selection for more dimorphic anthers, which may be a mechanism to limit pollen removal during a single visit (Conner et al 2003), may occur in environments where pollinators are reliably present and where pollinators differ in their effectiveness (Thomson and Thomson 1992).Both our finding of selection on dimorphism by only one pollinator, and similar selection on flower size by multiple pollinators, reveal that a generalist species can evolve to be well adapted to multiple pollinators. Our results for anther exsertion, however, suggest conflicting selection by small versus large bees.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Thus, if pollen removal is correlated with seed-siring success, this would mean selection to decrease dimorphism and could explain why honey bees select for decreased dimorphism. However, selection for more dimorphic anthers, which may be a mechanism to limit pollen removal during a single visit (Conner et al 2003), may occur in environments where pollinators are reliably present and where pollinators differ in their effectiveness (Thomson and Thomson 1992).Both our finding of selection on dimorphism by only one pollinator, and similar selection on flower size by multiple pollinators, reveal that a generalist species can evolve to be well adapted to multiple pollinators. Our results for anther exsertion, however, suggest conflicting selection by small versus large bees.…”
mentioning
confidence: 58%
“…Functional studies of pollen removal (Conner et al 1995) showed that honey bees and cabbage butterflies removed more pollen from wild radish flowers with increasing anther exsertion, whereas small bees removed most from plants with intermediate anther exsertion. Conner et al (2003) also found selection on stamen dimorphism during one year when honey bees were common, but did not find selection on this trait when honey bees were rare. These previous findings suggest that floral traits of wild radish may be under differential selection by different pollinators.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Most wild radish floral correlations are low to moderate (0.28 -0.59), with the exception of the three correlations among the short and long filaments (the filaments mainly determine the length of the stamens) and the corolla tube ( [22]; table 2). We have evidence for stabilizing selection through lifetime male seed siring success on the difference in lengths between the long filament and corolla tube (anther exsertion; [24]) and on the difference in lengths between the two filaments [25]. Stabilizing selection on the difference between two traits is evidence for correlational selection to increase the correlation between the two traits [26,27].…”
Section: Discussionmentioning
confidence: 94%
“…This implies that dispensing was effectively limiting pollen delivery, as pollen presentation theory predicts in plants with high visitation rates. Conner et al (2003) speculated that selection for restricted pollen removal might explain stasis in anther height dimorphism in the Brassicaceae. The flowers are usually generalists visited by small insects, and single-visit removal is reduced by anther dimorphism.…”
Section: Discussionmentioning
confidence: 99%